Designation of a neotype for the Brazilian porcupine, Coendou prehensilis (Linnaeus, 1758) - Leite, Yuri L. R.; Júnior, Vilacio Caldara; Loss, Ana Carolina; Costa, Leonora Pires; Melo, Éverton R. A.; Gadelha, José Ramon; Pontes, Antonio Rossano M. (Zootaxa, 2011)
The Brazilian porcupine was one of several species described and illustrated by the 17 th -century naturalist Georg Marcgrave, whose text was among the primary references upon which Linnaeus based his Hystrix prehensilis. As currently understood, Coendou prehensilis is a wide-ranging polytypic taxon that has never been revised and may represent a complex of closely related species. Given that no name-bearing type specimen of C. prehensilis is believed to be extant, and in order to avoid ambiguous application of this name, we designate a specimen collected at the type locality in Pernambuco, northeastern Brazil, as the neotype for Hystrix prehensilis Linnaeus. The geographic distribution of mitochondrial DNA haplotypes suggests that specimens from west-central Brazil previously identified as “Coendou prehensilis” belong to a different species, but only a comprehensive taxonomic revision of the genus will shed light on species limits and the geographic ranges of C. prehensilis and other congeneric forms.